Resistência punk no município de Cariacica/ES : uma narrativa estética, musical e teatral no meio underground - Alves, Sandriani Muniz (2019)
In this research, I intend to interpret the historical, cultural, musical narratives and the aesthetic and political experiences that guided the punk movement in the city of Cariacica-ES. I present this route from the productions of the 1980-90 and its current repercussions, in which I emphasize the remarkable performances of the bands Zoopatia, RHC and the Motim Theater Group. Thus, I intend to discuss the facts that I consider important in the punk scene of the studied municipality, as well as their implications in the social construction of the subjects that make up this community. To understand the reception of this style, I present some historical aspects in order to draw an overview of the theme. In this bias, I also highlight the legacy of the band Wound Exposed, whose production goes back to the initial phase of the movement in the capital city of Vitória. Indeed, common yearnings encourage the formulation of the punk movement in the state of Espírito Santo, which was born concurrently with the underground resistance in Cariacica. To complement this scenario, I present notes that I consider relevant to understand the variants expressed from the establishment and popularization of the movement in the United States, England and Brazil. In addition, I highlight the punk influence on the Riot Theater Group, analyzing one specific piece that reveal the multi-faceted character of the movement governed by the sign of resistance. The scripts and spectacles criticize the relations of the capitalist system and imperialism, further demonstrating the imbrications and conditioning of the cultural, political, economic, aesthetic and ideological fields. To analyze these issues, I support myself in the interpretations of Antonio Bivar, Luiz Carlos Maciel, Silvio Essinger, Gerd Bornheim, Noam Chomsky, Augusto Boal, David Le Breton, George Woodcock and Raphael Genuíno de Araújo, as well as reports, graphic materials and and interviews given by some of the members of the bands Zoopatia, RHC and the Motim Theater Group.